Diagnóstico precoce do câncer de mama em mutirões de mamografia no estado de São Paulo - Criado, Divanei Aparecida Bottaro (2014)
Introduction: Currently, breast cancer is the most common malignancy in women, being a public health issue. Objective: To assess the early diagnosis of breast cancer in mammography campaigns in São Paulo State by considering demographical and radiological data, as well as the association between age and BI-RADS classification. Patients and Method: A total of 1,015,508 mammography campaign examinations that were performed by women between May 2005 and November 2009 in municipalities of the 17 Regional Health Divisions (DRS) of Sao Paulo State were assessed. The mammogram results were analyzed according to the BI-RADS radiological classification. Chi-square tests with Yates or Fisher corrections were used to verify a possible association between age and BI-RADS classification. The relative likelihood of associations between lesions classified as categories 1 and 2 (benign), 4 (suspicious for malignancy) and 5 (highly suggestive of malignancy) and the patient age group (up to 39 and above 40 years, up to 49 years and above 50 years, and between 40-49 and 50-59 years of age) was assessed according to the Odds Ratio (OR). Results: In Sao Paulo State, with respect to age, there was a predominance of the fifth and sixth decades of life, totaling 379,561 and 311,020 mammograms, respectively (71.7%). Radiological findings obtained in the campaigns showed that the category 0 was found in 122 332 (12.0%) examinations; in category 1, 412,020 (40.6%) examinations showed no radiographic alterations; category 2 was the most common, being found in 436,099 (42.9%) examinations; the total mammograms in category 3 were 39,871 (3.9%); category 4 was observed in 4435 (0.4%) examinations, and category 5 was obtained in 751 mammograms (0, 1%). The frequency of occurrence of categories 4 + 5 (suspicious for malignancy) increased in parallel to increasing age. By analyzing the possible association between age and BI-RADS classification using a cutoff of up to 39 years against 40 years or more, there was a significant difference between the groups, both with respect to category 5 (P <0.0001) and the categories 4+5 (P <0.0001), as compared to categories 1 +2. The Odds Ratio of categories 4 and 5 appear in mammogram results of patients aged 40 or more was 56% higher than among those with up to 39 years (OR, 1.56; 95% Confidence Interval (CI), 1.36 to 1.79). Conclusions: Mammography campaigns performed in the São Paulo State contributed to the early diagnosis of breast cancer. There was a gradual increase in population participation in these campaigns over the studied period. Predominant age groups were the fifth and sixth decades of life. Radiological findings showed that the most frequent categories were 1 and 2, being 4 and 5 the least frequent. The increase in the frequency of BI-RADS categories 4 and 5 coincided with increasing age. The Odds Ratio of mammograms with categories 4 and 5 appear in patients aged 40 or more is 56% higher than among those with up to 39 years, indicating that the recommended age for mammogram evaluation should be for women aged 40 or more.